Implementasi Algoritma Dijkstra pada Aplikasi Go-Tahu dengan Pencarian Rute Terpendek ke Pabrik Tahu - Sari, Putriana Mayang; Fauziah, Fauziah; Gunaryati, Aris (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Currently, the food business sector is increasing, one of which is tofu producers in South Tangerang. Many people who want to buy tofu of good quality but do not know the closest distance to the factory is located. In this research, we will use Dijkstra’s Algorithm which is applied to the Android software to determine the shortest distance from one point to the tofu factory which is the chosen destination. Using the Dijkstra algorithm, an application will be designed, namely a mobile-based Go-Tofu for finding the closest route to the tofu factory. The route search process is carried out with a graph that has a weight and an area that is connected to a predetermined route. In the application test, it produces the shortest route from a house to the tofu factory with the smallest total weight of 11 kilometers based on the test results in the study.